Strategic planning and its relationship to the degree of university administration practice for heads of departments at Wasit University - سعد نعيم رضوي, د. (lark, 2020)
The study aimed to identify the level of strategic planning and the degree of   university administration practice for heads of departments at the University of Wasit from the faculty point of view and the relationship between them. The researcher adopted the relational descriptive approach. The research community consisted of (954) teaching in the Faculties of Education for Humanities and Pure Sciences. The research sample was chosen randomly, and the number of the sample members reached (200) teaching staff. A questionnaire was adopted that included (40) paragraphs distributed among the fields (future vision, laws and regulations, organizational structure, and implementation) for strategic planning and a questionnaire for university administration consisting of (45) paragraphs distributed between three areas and the researcher made sure of their validity and consistency. The results of the research data were analyzed using the (SPSS) program, and the researcher reached conclusions, including the level of strategic planning for department heads from the faculty point of view was average, and there were no differences attributable to the variable (gender, specialization) and the degree of university management practice was also moderate and the presence of a direct correlation between the two variables. Based on the results of the research, many recommendations were formulated.
Keywords: strategic planning, university administration, department heads, Wasit University.